The rules of wealth : a personal code for prosperity - Templar, Richard (Harlow, England ; New York : Pearson/Prentice Hall Business, 2007)
The rules of wealth analyses the behaviors, the mindsets, the lifestyles and the financial know-how behind becoming a richer, happier and more prosperous you. This book provides a set of principles, strategies and things to understand and to do that won$1 (Bt make you get rich quick, but they will increase the odds of your making money and growing your wealth while remaining a decent person. s
nmn 22/05/13
Loans
Keywords: Wealth - psychological aspects; Wealth - social aspects